COPD: Häusliche Rehabilitation ist eine Alternative zur ambulanten Reha (Die Rehabilitation, 2017)
Holland AE et al. Home-based rehabilitation for COPD using minimal resources: a randomised, controlled equivalence trial. Thorax 2016; doi: 10.1136/thoraxjnl-2016-208514